Short answer: 4 This question can be written out the long way. That will give you a better idea of how to get the answer. y= (-2)^2 can be written as y = (-2)(-2)
You should notice a couple of things. 1. The power of +2 means write everything inside the brackets twice. That includes the minus sign. 2. There is an even number of minus signs. That means that the answer will be +. If there was an odd number of minus signs (for example if the question was -(-2)^2 = - (-2 * -2) then the answer would be minus.
So there's an even number of minus signs in your question. The answer is 4.
The odd even rule is a good one to remember. <<<< 4 answer.
From the figure shown: Given that k=89, then: c=g=k=o=s=w=89 b=f=j=n=r=v=89 d=h=l=p=t=x=180-89=91 a=e=i=m=q=u=91 thus the sum of <span> s,e,q,u,o,i,a will be: </span>s+e+q+u+o+i+a =89+91+91+91+89+91+91 =633°